Advances in CAR T-cell therapy in bile duct, pancreatic, and gastric cancers - Feng, Qiang; Sun, Baozhen; Xue, Tianyi; Li, Rong; Lin, Chao; Gao, Yongjian; Sun, Liqun; Zhuo, Yue; Wang, Dongxu (Frontiers in Immunology, 2022)
Bile duct, pancreatic, and gastric cancers are deadly digestive system tumors with high malignancy and poor patient prognosis. The efficiencies of conventional surgical treatment, radiation therapy, and chemotherapy are limited. In contrast, chimeric antigen receptor (CAR) T-cell therapy represents a landmark therapeutic approach to antitumor immunity with great efficacy in treating several hematological malignancies. CAR T-cell therapy involves genetically engineering the expression of specific antibodies based on the patient’s T-cell surface and amplifying these antibodies to identify and target tumor-associated antigens. CAR T-cell therapy can effectively inhibit disease progression and improve the survival of patients with bile duct, pancreatic, and gastric cancers. The effectiveness of CAR T cells in tumor therapy can be validated using xenograft models, providing a scientific testing platform. In this study, we have reviewed the progress in CAR T-cell production and its development, focusing on the current status and optimization strategies for engineered CAR T cells in the bile duct, pancreatic, and gastric cancers.